PENGARUH PENAMBAHAN TEPUNG KUNYIT DAN BETAIN DALAM RANSUM TERHADAP VILI ILEUM, KECERNAAN PROTEIN DAN IMBANGAN EFISIENSI PROTEIN BABI PERIODE FINISHER (Effect of Dietary Turmeric Powder and Betaine Addition on Ileum Villi, Protein Digestion and Protein Efficiency Ratio of Finisher Pig) - Elnisi Br Mahulae; Sauland Sinaga; Denny Rusmana (Jurnal Ilmu dan Teknologi Peternakan, 2020)
Betaine and turmeric powder have the benefit of increasing digestibility and metabolism which affects the productivity of pig finisher period. The purpose of this study was to determine the effect and best dosage of betaine addition combined with turmeric powder in feed on ileum villi, protein digestion, and protein efficiency ratio of finisher period pig. The research was conducted experimentally according to a completely randomized design with 4 type of combination treatments of betain and turmeric powder in ration as follow: R0 = Basal feed, R1 = R0 + 0.4% turmeric powder + 0.1% betaine, R2 = R0 + 0.4% turmeric powder + 0.15% betaine, R3 = R0 + 0.4% turmeric powder + 0.2% betaine. Each treatment was repeated five times. The variables observed were ileum villi, protein digestion, and protein efficiency ratio. The results of the research showed that the treatments had a significant effect on the number of ileum villi, protein digestion, protein efficiency ratio, and. The addition of 0.15% betaine combined with 0.4% turmeric powder (R2) in feed showed the best effect on the ileum villi, protein digestion, and protein efficiency ratio of pig finisher period